Pre‐Columbian fisheries catch reconstruction for a subtropical estuary in South America. Issue 6 (29th August 2019) - Fossile, Thiago; Ferreira, Jessica; da Rocha Bandeira, Dione; Figuti, Levy; Dias‐da‐Silva, Sérgio; Hausmann, Niklas; Robson, Harry K.; Orton, David; Colonese, André Carlo
Abstract: Small‐scale fisheries provide food and livelihoods for thousands of people along the Brazilian coastline. However, considerable uncertainties still surround the extent to which artisanal and subsistence fisheries contribute to the total of national landings and their historical ecological significance. Fisheries monitoring is deficient in Brazil, and historical records are limited to irregular accounts spanning the last few decades, while this coastline has supported human populations for at least 6, 000 years. Here, we estimate pre‐Columbian subsistence catches for a large subtropical estuary in southern Brazil. Our results suggest that prehistoric populations may have extracted volumes of fish biomass higher than or comparable with historical subsistence fisheries in the region, and that the latter is likely underestimated. If a long‐term perspective is required to evaluate the current economic value and status of fisheries in subtropical and tropical South America, this should go beyond the historical time interval and integrate the contribution of pre‐Columbian archaeology.